Reinterpretasi Kisah Adam dan Hawa dalam Al-Qur’an - Ach Badri Amin; Fathurrosyid Fathurrosyid; Wardatun Nadhiroh (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
The story of Adam and Hawa is mentioned in various chapters of the Qur’an. The author is interested in examining this narrative, particularly regarding the truth of whether they were placed in His paradise. Different understandings from some commentators understand that they are in the paradise of the afterlife as a place of reward, while others understand it only as a worldly symbol. This study uses Michael Riffaterre’s semiotic approach which includes two reading models: heuristic and retroactive. This type of research is library research with a focus on the verses of the Qur’an related to the story of Adam and Hawa in paradise until their expulsion and descent to earth. The results of the heuristic reading show that Adam dan Hawa are in paradise by obeying the commands and avoiding the prohibitions, especially avoiding not approaching the tree in paradise. Meanwhile, the retroactive reading of al-Jannah is not paradise of the afterlife but rather a symbol of worldly pleasures, the violation of which is a transition of status that implies a fall from glory and then receiving forgiveness from Allah until being appointed as a prophet.